(untitled) (Research, Society and Development, 2020)
The form of improper disposal of solid household waste is one of the challenges for global environmental security. In this context, this article seeks to evaluate the performance of the aerobic biological treatment applied to the putrescible organic fraction of household solid waste generated in a vertical residential condominium. The experimental system consisted of two types of composters and three repetitions for each type with a 30 kg capacity. The physical, chemical and sanitary parameters used in the research were temperature, aeration, moisture content, total solids, total volatile solids, total nitrogen, total phosphorus, potassium, pH and helminth eggs. The results of the research present significant values ​​of the physical and chemical parameters obtained in the aerobic bio-stabilization process and the generation of organic compost within a good quality standard. For the amount of helminth eggs, it suffered a significant reduction, starting at 4.6 eggs/gTS and no helminth eggs were found in the organic compound produced. Thus, the aerobic biological treatment contributed to the nutrient cycling process, enabling the transformation of a major environmental and public health problem, into a sustainable solution in the economic and social environmental field.